Influence of eating habits of children with Autistic Spectrum Disorder (ASD) (Research, Society and Development, 2022)
Children with ASD are more likely to have eating difficulties, such as refusing and choosing certain foods, oral motor dysfunction and various behavioral problems. In addition, they may have essential micronutrient deficiencies compared to other children in the same developmental range. To verify the eating habits of children with Autism Spectrum Disorder (ASD).  An integrative review was carried out based on the PICo strategy. The search for articles was carried out in the PubMed, Scielo, Lilacs databases, using the descriptors in Portuguese and English: “Food selectivity”, “Habits” and “Autistic spectrum disorder” joined with the Boolean operator “AND”. Access to the databases was carried out from February to April 2022. 185 articles were found and after applying the inclusion criteria, 12 articles remained. It was noticed that children with Autism Spectrum Disorder (ASD) have a predisposition to food selectivity behaviors, which can indicate nutritional problems, a worrying factor, given that the childhood stage has a direct long-term influence. It is necessary that these children receive adequate intervention with regard to nutritional monitoring. The main eating habits in children with Autism Spectrum Disorder (ASD) are behaviors of food selectivity, resistance to trying new foods, reading variation, behavioral problems at mealtimes, where such food preferences are attributed to the influence of other factors, such as sensory sensitivity and family diet.